Megalodon, mako shark and planktonic foraminifera from the continental shelf off Portugal and their age - Antunes, Miguel Telles (2016)
Turbidite fragments collected by a fishing net off the central Portuguese coast (Peniche) present some fossils. The matrix is phosphatized and iron-rich with small quantities of manganese, zinc and copper. The occurrence of Megaselachus megalodon most probably excludes an age older than Middle Miocene. Its very advanced evolution stage is consistent with a Pliocene age. Based on planktonic foraminifera in depressions of cetacean skulls recovered in the same way, from the same area, the age of sharks and cetaceans is likely to range from latest Messinian to Early Pliocene. Condensed sedimentation is revealed by the co-occurrence of typical Late Pliocene and Quaternary foraminifera. Lack of benthic foraminifera suggests more or less deep environments, while a scallop, Mimachlamys varia, indicates nearby rocky substrate. The mako shark Isurus cf. oxyrhinchus is recorded in the area for the first time. The shark association represents a moderately warm environment as M. megalodon and Isurus are essentially temperate water dwellers, while no warm water form is known. Early Pliocene planktonic foraminifera point out to temperate to subtropical waters. Hence temperate to moderately warm conditions seem to have prevailed.